Luminal STIM1 Mutants that Cause Tubular Aggregate Myopathy Promote Autophagic Processes - Sallinger, Matthias (Int J Mol Sci, 2020)
Stromal interaction molecule 1 (STIM1) is a ubiquitously expressed Ca(2+) sensor protein that induces permeation of Orai Ca(2+) channels upon endoplasmic reticulum Ca(2+)-store depletion. A drop in luminal Ca(2+) causes partial unfolding of the N-terminal STIM1 domains and thus initial STIM1 activation. We compared the STIM1 structure upon Ca(2+) depletion from our molecular dynamics (MD) simulations with a recent 2D NMR structure. Simulation- and structure-based results showed unfolding of two α-helices in the canonical and in the non-canonical EF-hand. Further, we structurally and functionally evaluated mutations in the non-canonical EF-hand that have been shown to cause tubular aggregate myopathy. We found these mutations to cause full constitutive activation of Ca(2+)-release-activated Ca(2+) currents (I(CRAC)) and to promote autophagic processes. Specifically, heterologously expressed STIM1 mutations in the non-canonical EF-hand promoted translocation of the autophagy transcription factors microphthalmia-associated transcription factor (MITF) and transcription factor EB (TFEB) into the nucleus. These STIM1 mutations additionally stimulated an enhanced production of autophagosomes. In summary, mutations in STIM1 that cause structural unfolding promoted Ca(2+) down-stream activation of autophagic processes.